Branched Aramid Nanofibers. (18th August 2017) - Zhu, Jian; Yang, Ming; Emre, Ahmet; Bahng, Joong Hwan; Xu, Lizhi; Yeom, Jihyeon; Yeom, Bongjun; Kim, Yoonseob; Johnson, Kyle; Green, Peter; Kotov, Nicholas A.
Abstract: Interconnectivity of components in three‐dimensional networks (3DNs) is essential for stress transfer in hydrogels, aerogels, and composites. Entanglement of nanoscale components in the network relies on weak short‐range intermolecular interactions. The intrinsic stiffness and rod‐like geometry of nanoscale components limit the cohesive energy of the physical crosslinks in 3DN materials. Nature realizes networked gels differently using components with extensive branching. Branched aramid nanofibers (BANFs) mimicking polymeric components of biological gels were synthesized to produce 3DNs with high efficiency stress transfer. Individual BANFs are flexible, with the number of branches controlled by base strength in the hydrolysis process. The extensive connectivity of the BANFs allows them to form hydro‐ and aerogel monoliths with an order of magnitude less solid content than rod‐like nanocomponents. Branching of nanofibers also leads to improved mechanics of gels and nanocomposites.